New records of the genera Acerentulus and Brasilidia (Protura: Acerentomidae) from China, with descriptions of two new species - Wu, Dong Hui; Yin, Wen Ying (Zootaxa, 2007)
Two new species, Acerentulus sinensis sp. nov. and Brasilidia jilinensis sp. nov., from Jilin Province, northeastern China, are described and illustrated in the present paper. All specimens are deposited in Shanghai Entomological Museum (SEM), Institute of Plant Physiology & Ecology, Shanghai Institutes for Biological Sciences, Chinese Academy of Sciences.